Automated Integration of Dedicated Hardwired IP Cores in Heterogeneous MPSoCs Designed with ESPAM. (15th April 2008) - Nikolov, Hristo; Stefanov, Todor; Deprettere, Ed
Abstract : This paper presents a methodology and techniques for automated integration of dedicated hardwired (HW) IP cores into heterogeneous multiprocessor systems. We propose an IP core integration approach based on an HW module generation that consists of a wrapper around a predefined IP core. This approach has been implemented in a tool called ESPAM for automated multiprocessor system design, programming, and implementation. In order to keep high performance of the integrated IP cores, the structure of the IP core wrapper is devised in a way that adequately represents and efficiently implements the main characteristics of the formal model of computation, namely, Kahn process networks, we use as an underlying programming model in ESPAM. We present details about the structure of the HW module, the supported types of IP cores, and the minimum interfaces these IP cores have to provide in order to allow automated integration in heterogeneous multiprocessor systems generated by ESPAM. The ESPAM design flow, the multiprocessor platforms we consider, and the underlying programming (KPN) model are introduced as well. Furthermore, we present the efficiency of our approach by applying our methodology and ESPAM tool to automatically generate, implement, and program heterogeneous multiprocessor systems that integrate dedicated IP cores and execute real-life applications.